Pemanfaatan Lumpur Sungai Ciliwung Dengan Metode Solidifikasi - Chaerul Mochammad; Roy Jeremiah Pasaribu (Dampak, 2020)
Sediment potentially leads to siltation of the river and overflow of river water during the rainy season.  Existing management of the sediment is to collect, transport and dispose in a site without any proper handling procedure prior and it may cause environment burden. This study aims to utilize the sediment in Ciliwung river as a structural material through a set of solidification procedure. The mixing of cement and fine aggregate is necessary to produce 5x5x5 cm3 mortar to be tested. The sediment may be classified as non-hazardous waste and it can be used to substitute sand as the fine aggregate. The highest compressive strength of 216 kg/cm2 can be produced at ratio of cement and the fine aggregate of 1:3 with the sediment substitution of 50% and the product can be classified as class B of paving block or class I of brick. Through Toxicity Characteristic Leaching Procedure (TCLP) test, it find that the metals substance in the sediment bounded properly in the solid matrix and it prevents the metals leaching out to the environment. The study reveals that the utilization of the sediment through the solidification become a prospective measure by producing a useful product with minimum impact on the environment. Keywords: Sediment, fine aggregate, solidification, compressive strength, Toxicity Characteristic Leaching Procedure  ABSTRAK  Lumpur berpotensi menyebabkan pendangkalan sungai dan meluapnya air sungai selama musim hujan. Manajemen lumpur yang ada adalah mengumpulkan, mengangkut, dan membuang di lokasi tanpa prosedur penanganan yang tepat sebelumnya dan dapat membebani lingkungan. Penelitian ini bertujuan untuk memanfaatkan lumpur di sungai Ciliwung sebagai material struktural melalui serangkaian prosedur pemadatan. Pencampuran semen dan agregat halus diperlukan untuk menghasilkan mortar 5x5x5 cm3 untuk diuji. Lumpur dapat diklasifikasikan sebagai limbah tidak berbahaya dan dapat digunakan untuk menggantikan pasir sebagai agregat halus. Kuat tekan tertinggi 216 kg/cm2 didapat  pada rasio semen dan agregat halus 1: 3 dengan substitusi sedimen 50% dan produk dapat diklasifikasikan sebagai paving block kelas B atau bata kelas I. Melalui uji Toxicity Characteristic Leaching Procedure (TCLP), ditemukan bahwa zat logam dalam lumpur terikat dengan benar dalam matriks padat dan mencegah logam berpindah ke lingkungan. Dari penelitian ini, didapatkan bahwa pemanfaatan lumpur sungai dengan pemadatan berpotensi  menghasilkan produk yang bermanfaat dengan dampak minimal terhadap lingkungan. Kata kunci: Lumpur, Agregat halus, Solidifikasi, Kuat tekan, Toxicity Characteristic Leaching Procedure